AN ANALYSIS OF FIGURATIVE LANGUAGE IN SELECTED HARDY’S POEMS - Jaya Kurnia Sandy; M. Natsir; Chris Asanti (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2021)
This study is focused on the types and the meaning of figurative language used in the selected Hardy’s poems. The poems are Rain on a Grave, Her Immortality, The Spell of Rose and The-To-Be-Forgotten. By using descriptive qualitative method, this study purposed to answer the following questions. The first research question is what kinds of figurative language are used in four selected Hardy’s poems. The second research question is what are the meanings of figurative language used in four selected Hardy’s poems. The result of the analysis using Perrine’s theory showed that four selected Hardy’s poems contain 24 figurative languages. From the analysis, there are 9 types of figurative languages that appear such as, simile, metaphor, personification, apostrophe, synecdoche, metonymy, symbol, hyperbole and understatement. By analyzing the figurative language, the researcher is able to define the meaning of the lines that contain figurative language.